Neospora caninum: a new class of biopharmaceuticals in the therapeutic arsenal against cancer. Issue 2 (30th November 2020) - Lantier, Louis; Poupée-Beaugé, Agathe; di Tommaso, Anne; Ducournau, Céline; Epardaud, Mathieu; Lakhrif, Zineb; Germon, Stéphanie; Debierre-Grockiego, Françoise; Mévélec, Marie-Noëlle; Battistoni, Arthur; Coënon, Loïs; Deluce-Kakwata-Nkor, Nora; et al.
Abstract : Background: Microorganisms that can be used for their lytic activity against tumor cells as well as inducing or reactivating antitumor immune responses are a relevant part of the available immunotherapy strategies. Viruses, bacteria and even protozoa have been largely explored with success as effective human antitumor agents. To date, only one oncolytic virus—T-VEC—has been approved by the US Food and Drug Administration for use in biological cancer therapy in clinical trials. The goal of our study is to evaluate the potential of a livestock pathogen, the protozoan Neospora caninum, non-pathogenic in humans, as an effective and safe antitumorous agent. Methods/Results: We demonstrated that the treatment of murine thymoma EG7 by subcutaneous injection of N. caninum tachyzoites either in or remotely from the tumor strongly inhibits tumor development, and often causes their complete eradication. Analysis of immune responses showed that N. caninum had the ability to 1) lyze infected cancer cells, 2) reactivate the immunosuppressed immune cells and 3) activate the systemic immune system by generating a protective antitumor response dependent on natural killer cells, CD8-T cells and associated with a strong interferon (IFN)-γ secretion in the tumor microenvironment. Most importantly, we observed a total clearance of the injected agent in the treated animals: N. caninum exhibited strong anticancer effects without persisting in the organism of treated mice. We also established in vitro and an in vivo non-obese diabetic/severe combined immunodeficiency mouse model that N. caninum infected and induced a strong regression of human Merkel cell carcinoma. Finally, we engineered a N. caninum strain to secrete human interleukin (IL)-15, associated with the alpha-subunit of the IL-15 receptor thus strengthening the immuno-stimulatory properties of N. caninum . Indeed, this NC1-IL15hRec strain induced both proliferation of and IFN-γ secretion by human peripheral blood mononuclear cells, as well as improved efficacy in vivo in the EG7 tumor model. Conclusion: These results highlight N. caninum as a potential, extremely effective and non-toxic anticancer agent, capable of being engineered to either express at its surface or to secrete biodrugs. Our work has identified the broad clinical possibilities of using N. caninum as an oncolytic protozoan in human medicine.